the Antibacterial and antifungi activity of pandan wangi (Pandanus amaryllifolius Roxb)leaf ethanolic extract and its n-heksan and etil acetate fraction - Setiyanto, Riyan; Suhesti, Iin; Utami, Annisa Dwi (Jurnal Ilmiah Farmasi, 2024)
Background: Pandanus amaryllifolius Roxb leaves are commonly used as a food additive, green coloring agent, and flavor enhancer. Additionally, these leaves are renowned in herbal medicine for their potential to inhibit cancer cell growth, relieve diarrhea, and act as antioxidants. The leaves contain alkaloids with promising antibacterial and antifungal properties.Objective: This research aimed to evaluate the inhibitory zone activity of leaf extract (ethanol), n-hexane, and ethyl acetate fractions against methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, and Candida albicans.Method: The maceration method was used for extraction, employing a 70% ethanol solution as the solvent. The ethanol extract was then fractionated using n-hexane and ethyl acetate. The Kirby-Bauer disc diffusion method was applied to assess the antibacterial and antifungal activity of the extracts and fractions. The diameter of the inhibition zones was measured and analyzed statistically.Result: The ethanol extract demonstrated the strongest antibacterial activity against MRSA compared to the n-hexane fraction and the ethyl acetate fraction. None of the concentration variations significantly inhibited the growth of Escherichia coli and Candida albicans.Conclusion: The ethanolic extract of Pandanus amaryllifolius Roxb leaves shows potential as an antibacterial agent against methicillin-resistant Staphylococcus aureus.Keywords: Pandanus amaryllifolius Roxb., 70% ethanol extract, fractionation, disc diffusion method, MRSA IntisariLatar belakang: Daun Pandanus amaryllifolius Roxb umumnya digunakan sebagai komponen tambahan makanan zat pewarna hijau dan penambah rasa. Daun ini telah dikenal luas sebagai obat herbal yang mempunyai potensi menghambat pertumbuhan sel kanker, meringankan diare, berkhasiat sebagai antioksidan. Kandungan daunnya mengandung alkaloid yang berpotensi menunjukkan efek antibakteri dan antijamur. Tujuan: Penelitian ini untuk mengukur aktivitas zona hambat dari ekstrak daun (etanol), fraksi n-heksan dan etil asetat terhadap Staphylococcus aureus resisten methicillin, Escherichia coli, dan Candida albicans. Metode: Metode maserasi digunakan untuk mengekstraksi. Pelarut yang digunakan adalah larutan yang terdiri dari 70% etanol. Ekstrak etanol dilakukan fraksinasi n-heksan dan etil asetat. Metode difusi cakram Kirby-Bauer digunakan uji aktivitas diagnostik antibakteri dan antijamur. Diameter zona hambat kemudian diukur dan dilakukan analisis statistik. Hasil: Ekstrak daun (etanol) memperlihatkan daya antibakteri yang paling kuat terhadap MRSA dibandingkan fraksi n-heksana dan fraksi etil asetat. Variasi konsentrasi secara substansial mengurangi pertumbuhan Escherichia coli dan Candida albicans.Kesimpulan: Ekstrak daun Pandanus amaryllifolius Roxb yang dilarutkan dalam pelarut etanol 70% memiliki potensi antibakteri untuk Staphylococcus aureus yang resisten terhadap methicillin. Kata kunci: Pandanus amaryllifolius Roxb, ekstrak etanol 70%, fraksinasi, metode difusi cakram, MRSA